Estado de la cuestión sobre la tipología del impreso antiguo español (ss. XV-XIX) - González-sarasa, Silvia (Revista General de Información y Documentación, 2009)
This article realizes a tour through the studies published up to the moment on typology of the ancient Spanish printing, analyzing briefly the most out-standing. Likewise, it justifies the importance of the achievement of a work that gathers the whole production printed between the XVth and XVIIIth centuries.
Keywords: Printing; Typology; Bibliography